Evaluation of Character Education Strengthening Program through Scouts Extra in KKSC (Kisada Kids Scout Camp) Activities Using Countenance Evaluation at MIS Ushuluddin Singkawang - Masruraini Masruraini; Muhammad Nur Akbar Rasyid; Sitti Mania (International Journal of Multi Discipline Science (IJ-MDS), 2023)
This research aimed to evaluate the KKSC program at MIS Ushuluddin Singkawang using the Countenance Stake model. KKSC is a camp held by MIS Ushuluddin to develop children's character through Scout activities. This research was a program evaluation study using a qualitative descriptive approach. The evaluation model used was the Countenance Stake model involving three stages, namely the antecedent, transaction, and outcomes stages. This research was conducted at MIS Ushuluddin Singkawang. Data collection techniques used documentation, observation and direct interviews with scout leaders, homeroom teachers, parents, and students at MIS Ushuluddin Singkawang. The results of the research found that KKSC activities as one of the Scouting activities in the context of strengthening student character at MIS Ushuluddin Singkawang had gone well, both in terms of planning and implementation, resulting in good strengthening of character education as expected.